Case law review 5th Chamber Supreme Court - Reyes López, Javier Ignacio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2026)
STS 621/2025, 2 July. Determination of the moment of police custody in a judicially authorised entry and search. 2. STS 814/2025, 8 October. Requirements of unlawfulness in environmental matters, in order to distinguish between sanctioning regulations of an administrative nature and criminal types. 3. STS 837/2025, 15 October. Validity of the police inspection of warehouses and other places that do not constitute a home, even when there were areas for private life that were not subject to search. 4. STS 797/2025, 2 October. Occasional capture by the police of images in a semi-private area, through the use of a drone, as an adjuvant element to the request for a home search. 5. STS 854/2025, 16 October. Analysis of the validity of the evidence obtained in France through the Encrochat application, a closed network of communication through encrypted messages. 6. STS 861/2025, 22 October. Undercover agents. Provision in their entirety of the recorded conversations. 7. STS 849/2025, 16 October. Disclosure of secrets by a public official. Fraudulently obtaining access codes to a computer. 8. STS 866/2025, 22 October. Self-consumption or trafficking of GBL. Questionable minimum doses.